Spontaneous hepatic rupture: a report of five cases - Mascarenhas, R (2002)
Background Spontaneous hepatic rupture is a well recognised but rare condition. Because of the difficulty in diagnosis, it is often associated with a high mortality rate. Pregnant women with HELLP syndrome are more prone to hepatic rupture, but it can also occur with other liver pathology. Different modalities of treatment, including liver resection, packing, hepatic artery ligation and even liver transplantation have been described for this condition. Patients and results We report a series of five cases, three of which were associated with pregnancy and two with no identifiable pathology. Pre-operative diagnosis was not made in any of these cases.Two of the five patients had hepatic resection, two had peri-hepatic packing and one was treated with laparoscopic drainage. Discussion From our experience we conclude that no single form of treatment is applicable to all cases of hepatic rupture.The treatment should be individualised,depending on the extent of hepatic rupture and the expertise available, to obtain best outcome.